Capacity‐enhancement in MIMO systems using biomimetic electrically small antenna arrays. Issue 13 (24th July 2018) - Ranjbar Nikkhah, Mohammad; Panahi, Mohammad Ali; Luyen, Hung; Bahrami, Hamid; Behdad, Nader
Abstract : The authors investigate the performance of multi‐input–multi‐output (MIMO) communications systems that exploit biomimetic antenna arrays (BMAAs) with electrically small‐aperture dimensions. By exploiting the mutual coupling between closely spaced radiating elements and extracting the maximum available power from all excitation modes of the array, BMAAs can significantly outperform conventional antenna arrays with similar aperture sizes. As a proof of concept demonstration, they examine the use of two‐element BMAAs consisting of two λ / 4 monopole antennas with variable element spacing in an MIMO system. The capacity of MIMO systems using such BMAAs is compared with those that use conventional antenna arrays with the same element types and spacing. Their simulation results demonstrate that using BMAAs can offer considerable capacity enhancements in an MIMO system. To experimentally verify these results, a prototype of a two‐element BMAA operating at 615 MHz with element spacing of λ / 10 and a regular array prototype with similar antenna elements and dimensions are fabricated and characterised. The performance of MIMO systems using these two antennas is modelled using numerical channel modelling using the measured antenna responses. These results are found to be in good agreement with theoretical predictions.